Clinical profile and outcome of patients admitted to pediatric intensive care unit in a tertiary care teaching hospital of Puducherry, India - K., Maheswari; Sharma, Neha (International Journal of Contemporary Pediatrics, 2020)
Background: This study was undertaken to know about the clinical profile and outcome of patients admitted in paediatric ICU in a tertiary care teaching hospital. Methods: This is a hospital based, retrospective, descriptive study, done on patients admitted to paediatric ICU of Sri Venkateshwara Medical College Hospital and Research Centre Puducherry from Jan 2019 - Dec 2019 (12 months). Results: As about 424 patients were admitted paediatric ICU. 79 patients were excluded from the study. Remaining 345 PICU patients were analysed. According to the age distribution of patients, it showed that < 1year were (25.2%), 1-5 years were (44.3%), > 5years of age were (30.4%). There was a female preponderance (58.8%), males were (41.1%). Patients from rural area were 243 (70.4%) and 102 (29.5%) from urban area. Clinical profile showed that pneumonia was the most common diagnosis (8.4%) for admission in PICU. This was followed by bronchiolitis (6.9%), enteric fever in (6.6%), febrile seizures (6.3%), poisoning (6.0%), renal problems (5.7%), occult bacteremia (5.5%), unknown bite (5.2%), acute severe asthma (4.9%), sepsis (4.6%), severe gastritis (4.3%), clinical dengue (3.7%), seizure disorder (3.4%), croup (3.1%), traumatic head injury (2.8%), wheeze associated LRI (2.6%), acute otitis media (2.3%), migraine (2.0%), meningitis (1.7%), CHD with complications (1.7%), severe anaemia with CCF (1.4%), acute urticarial (1.4%), foreign body (1.1%), electric shock (1.1%), scorpion sting (0.8%), viral hepatitis (0.8%), clinical malaria (0.8%), nephrotic syndrome with complications (0.5%), scrub typhus (0.2%) and (0.2%) was angioedema. The outcome noted was, (87.8%) were discharged, (10.7%) patients went against medical advice, (1.4%) patients were referred at parent’s request. Conclusions: Respiratory illness, infectious diseases, neurological problems and poisoning are the most common cause for PICU admissions. But seronegative dengue cases, electric shock, reemergence of scrub typhus, are being increasingly diagnosed. So, emphasis is therefore placed on high index of suspicion for this type of conditions. We also recommend better manpower and infrastructure to improve the outcome of patients admitted to PICU.